Whole-Genome Resequencing of Red Junglefowl and Indigenous Village Chicken Reveal New Insights on the Genome Dynamics of the Species - Lawal, Raman A.; Al-Atiyat, Raed M.; Aljumaah, Riyadh S.; Silva, Pradeepa; Mwacharo, Joram M.; Hanotte, Olivier (Frontiers in Genetics, 2018)
The red junglefowl Gallus gallus is the main progenitor of domestic chicken, the commonest livestock species, outnumbering humans by an approximate ratio of six to one. The genetic control for production traits have been well studied in commercial chicken, but the selection pressures underlying unique adaptation and production to local environments remain largely unknown in indigenous village chicken. Likewise, the genome regions under positive selection in the wild red junglefowl remain untapped. Here, using the pool heterozygosity approach, we analysed indigenous village chicken populations from Ethiopia, Saudi Arabia, and Sri Lanka, alongside six red junglefowl, for signatures of positive selection across the autosomes. Two red junglefowl candidate selected regions were shared with all domestic chicken populations. Four candidates sweep regions, unique to and shared among all indigenous domestic chicken, were detected. Only one region includes annotated genes (TSHR and GTF2A1). Candidate regions that were unique to each domestic chicken population with functions relating to adaptation to temperature gradient, production, reproduction and immunity were identified. Our results provide new insights on the consequence of the selection pressures that followed domestication on the genome landscape of the domestic village chicken.